Effect of the administration of probiotic Bacillus NP5 in the rearing media on water quality, growth, and disease resistance of African catfish (Clarias gariepinus) - Achmad Noerkhaerin Putra; Mas bayu Syamsunarno; Widia Ningrum; Jumyanah Jumyanah; Mustahal Mustahal (Society for Indonesian Biodiversity, 2020)
Abstract. Putra AN, Syamsunarno MB, Ningrum W, Jumyanah, Mustahal. 2020. Effect of the administration of probiotic Bacillus NP5 in the rearing media on water quality, growth, and disease resistance of African catfish (Clarias gariepinus). Biodiversitas 21: 2566-2575. The purpose of this study was to investigate the effect of administration of the probiotic Bacillus NP5 in rearing media on water quality, growth, and disease resistance of African catfish. The study consisted of three different concentrations of probiotic Bacillus NP5 - C: control, A: probiotic Bacillus NP5 of 1 x 109 CFU/mL, and B: probiotic Bacillus NP5 of 1 x 1010 CFU/mL, on the rearing media of African catfish for 45 days. Based on the results, the lowest significant ammonia (P <0.05) was found in treatment A (1.91 ± 0.17 mg/L), then followed by B (2.12 ± 0.14 mg/L) while the highest was in the control (2.36 ± 0.19 mg/L). Treatment A also had a better immune response compared to other treatments shown with the highest significant number of leukocytes at 6.69 ± 0.17 x 104 cells/mm3 and phagocyte activity at 65.19 ± 0.04%. Furthermore, treatment A significantly resulted in the best specific growth rate and feed conversion ratio (2.02 ± 0.07%.day-1, 1.05 ± 0.07, respectively). The administration of probiotic Bacillus NP5 of 1 x 109 CFU/mL in rearing media significantly improved the ammonia value, growth, and resistance of African catfish to Aeromonas hydrophila infection.